A religião no quadro da modernidade : duas possibilidades de abordagem a partir da obra de Jürgen Habermas - Oliveira, Lennimarx Porfírio (2018)
This work aims to analyze how Jürgen Habermas settles the phenomenon of religion in the frame of modernity according to a reading key that divides the configuration of this relation inside the author’s writings in two moments. In the first moment, the grasp proposed by Habermas assumes an inflection that brings into account the different stages of society, however without dodging to check the philosophical assumptions and consequences of the proposed theoretical model. We start from the theory of rationality advanced by Habermas: towards the elaboration of a concept of communicative rationality, the study of linguistically mediated interaction is intertwined with the concept of communicative action, which serves as bridge to a theory of society. Then, the concept of modernity embraced by Habermas is stressed in a way that gives emphasis to the maturing of structural components of modern society. At last, we expose how the process of rationalization which culminates in modernity progressively withdraws the structuring social functions performed by religion while advances the formation of a new faith awareness. At the second part, the endurance and the contribution of religion to modern societies are attested. At the beginning, we stress how Habermas conceptually articulates the relation between the structural components of society and what is the function ascribed by him to law in this process. Then, the Habermasian theory of law is explained in a way that emphasizes the reciprocal complementation between law and politics. We expose the specificity of Habermas’ conception of democracy and how it depends on communicatively articulated cognitive resources. In this context, religion has the unique capability of bringing up positive contributions: in a society that has shaped itself as post-secular, it is recognized that religion isn’t just a component of modernity among others, but also has a particular status which allows it to unleash normative contents in order to help maintaining modernity’s achievements. Finally, we explore the similarities and differences between both parts of this work and we accomplish a critical appraisal of the results achieved in the study of how Habermas sees the framing of religion by modernity.